3D focusing in simple microfluidic devices for continuous-flow single-cell imaging [data set] - Constantinou, Iordania; Jendrusch, Michael; Görlitz, Frederik; Schulze, André; Knop, Michael (Universität, 2018)
Accompanying data for the manuscript "3D Focusing in Simple Microfluidic Devices for Continuous-flow Single-cell Imaging".